2010
DOI: 10.1080/10913671003715516
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the New Lifestyles NL-1000 Accelerometer for Measuring Time Spent in Moderate-to-Vigorous Physical Activity in School Settings

Abstract: Current interest in promoting physical activity in the school environment necessitates an inexpensive, accurate method of measuring physical activity in such settings. Additionally, it is recognized that physical activity must be of at least moderate intensity in order to yield substantial health benefits. The purpose of the study, therefore, was to determine the validity of the New Lifestyles NL-1000 (New Lifestyles, Inc., Lee's Summit, Missouri, USA) accelerometer for measuring moderate-to-vigorous physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
15
1
1
Order By: Relevance
“…This study represents the second investigation of the accuracy of the NL-1000 pedometer for measuring minutes of MVPA in children. The first such study compared the performance of the NL-1000 with a uniaxial accelerometer (Actigraph GT1M) for detecting older children's MVPA during a cross-country run, physical education, and classroom-based physical activities (12). The authors concluded that the MVPA data recorded by the NL-1000 at intensity level 3 (£ 2.6 MET)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study represents the second investigation of the accuracy of the NL-1000 pedometer for measuring minutes of MVPA in children. The first such study compared the performance of the NL-1000 with a uniaxial accelerometer (Actigraph GT1M) for detecting older children's MVPA during a cross-country run, physical education, and classroom-based physical activities (12). The authors concluded that the MVPA data recorded by the NL-1000 at intensity level 3 (£ 2.6 MET)…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study has investigated the performance of the NL-1000 for assessing MVPA in children. McMinn et al (12) compared time spent in MVPA between the NL-1000 and a uniaxial accelerometer (Actigraph GT1M, Actigraph LLC, Pensacola, FL). Children aged 10-13 years wore the equipment under three different conditions (1): a cross-country run (N = 12) (2), physical education (N = 18), and (3) classroom activity breaks (N = 42).…”
mentioning
confidence: 99%
“…Measuring the intensity of the physical activity by using a pedometer [30], which is a portable device used to count steps that will be placed on the waist of children and secured with a belt while they participate in the physical education classes.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity used in this study was above 3.6 metabolic equivalents. Estimates of moderate to vigorous PA from the NL-1000 were found to be not meaningfully different from, and moderately to highly correlated with, other accelerometer-based measures of moderate to vigorous PA. 51,52 Participants were asked to wear the NL-1000 on the anterior area of their nondominant hip during all waking hours for seven continuous days and to return to the laboratory after 1 week. The times of day that participants put the monitor on and took the monitor off were recorded in a log.…”
Section: Physical Activitymentioning
confidence: 99%